The Use of Instagram and TikTok in the GEN SMART Program for Academic Writing Ethics Education: A Study of First Year Students - Nila Authoria; Darmawan, Mochammad Arief (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
Abstract: Ethical academic writing is a fundamental competency that should be developed early in higher education, particularly in health-related vocational education, where academic integrity is closely linked to professional ethics. This study aims to examine the use of Instagram and TikTok in the GEN SMART (Generasi Sadar Menulis Akademik Beretika) Program as social media–based educational platforms for promoting ethical academic writing among students of the Nutrition Department at Poltekkes Kemenkes Malang. A descriptive quantitative design with an evaluative approach was employed using non-participant digital observation to analyze interaction metrics on the Instagram and TikTok accounts @tulisituetis. Data included likes, saves, and views of educational content posted between 25–26 October 2025, with recapitulation conducted up to 27 October 2025. These quantitative data were supported by participant testimonials to strengthen the interpretation of engagement and program impact. The findings show that Instagram helps maintain consistent exposure to educational messages with stable engagement, while TikTok achieves higher audience reach and interaction due to its dynamic short-video format. Testimonials further indicate positive perceptions of the program, including increased awareness of academic ethics and integrity, as well as improved understanding of technical aspects of ethical academic writing.